Pemakaian Kaedah-Kaedah Fekah Dalam Institusi Fatwa Di Wilayah Persekutuan Dari Tahun 2010-2014 - Che Omar, Siti Nur Amalina; Mat Hussin, Mohd Norhusairi (Online Journal of Research in Islamic Studies, 2018)
The aims of this research is to identify and analyze the sources of Islamic law with is the Al-Qawa‘id Al-Fiqhiyyah that have always been used by the Islamic scholar and mujtahids at the time of development of this method, Further study also have been made to determine the application of this legal maxim applies in fatwa particularly in Wilayah Persekutuan Kuala Lumpur. This study was conducted by library research by referring to academic articles, books and Kitab that is relevant to this topic. Indirectly, the methods have given the author more understanding about the topic of research. To get more relevant result, field study had been conducted through interviews with the official of Istinbat and Buhuth Units at the mufti office of Wilayah Persekutuan Kuala Lumpur. Another method that have been used by the author in conducted this research is through the documentation of original documents such as minutes of meetings, paper works and research papers. The result showed that the application of Al-Qawa‘id Al-Fiqhiyyah in fatwa at fatwa Institution of Wilayah Persekutuan is not widely used, which is due to the issue that have been received by the mufti institution at Wilayah Persekutuan is basically a common question that have been discussed by the Islamic scholar in their books and Kitab. Studied have also shown that the application of Al-Qawa‘id Al-Fiqhiyyah tends to be used for matters that do not have nas or dalil with is involved the topic of al-darurah, al-hajat and al-maslahah.